2023
DOI: 10.3390/metabo13060709
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Metabolites and the Tumor Microenvironment as Potent Regulators of Cancer Stem Cell Signaling

Abstract: Individual cancer cells are not equal but are organized into a cellular hierarchy in which only a rare few leukemia cells can self-renew in a manner reminiscent of the characteristic stem cell properties. The PI3K/AKT pathway functions in a variety of cancers and plays a critical role in the survival and proliferation of healthy cells under physiologic conditions. In addition, cancer stem cells might exhibit a variety of metabolic reprogramming phenotypes that cannot be completely attributed to the intrinsic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“… 27 , 28 Fatty acid synthase (FASN) is involved in the whole process of de novo fatty acid synthesis and is highly expressed in many types of cancers. 29 , 30 Glucose metabolism, as the main source of cellular energy, is very important. Glycolysis is the main way of glucose metabolism, and its metabolite pyruvate can be converted into lactic acid, which can be secreted as the final product to the cell or enter the mitochondria for TCA cycle and oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 Fatty acid synthase (FASN) is involved in the whole process of de novo fatty acid synthesis and is highly expressed in many types of cancers. 29 , 30 Glucose metabolism, as the main source of cellular energy, is very important. Glycolysis is the main way of glucose metabolism, and its metabolite pyruvate can be converted into lactic acid, which can be secreted as the final product to the cell or enter the mitochondria for TCA cycle and oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that CSCs possess the capability to self-renew and differentiate, contributing to cancer recurrence, chemotherapy resistance, and tumor progression. Emerging studies have revealed an association between fatty acid metabolism and tumor stem cells [ 34 ]. Abnormal fatty acid metabolism is believed to provide an enhanced energy supply to sustain the maintenance of tumor stem cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%